RAINBOW OF COLOURS – THE PAHARI MINIATURE PAINTING” - Sonika (International Journal of Research -GRANTHAALAYAH, 2014)
Indian miniatures are in the art world a class by themselves. ‘Miniature’ generally refers to a painting or illumination, small in size, meticulous in detailing and delicate in brushwork1. Indian Miniature Painting has a long history of over thousand years and presents a comprehensive record of the religious and emotional feelings of the Indian people. These paintings show the Indian genius in its pure form. Its inspiration is rooted in the people’s hearts, keeping close to their poetry, music and drama. The great merit of this art is the exquisite delicacy of drawing with decorative details. The artists of these miniatures used bright colours with tempera effect and display an unusual understanding of colour combinations. Miniature art form made its debut in the 10th century. The earliest of miniatures are found painted on palm-leaves and their themes relating to Jainism and Buddhism. The palm-leaf paintings seem to have developed between 10th to 12th centuries. In the 14th century, palm leaf was replaced by paper and to earlier colours were added new mineral colours and pigments. Paper, with its tougher, smoother and better pigments absorbing surface almost revolutionized the entire art scenario2.